Improving berry quality and antioxidant ability in ‘Ruidu Hongyu’ grapevine through preharvest exogenous 2,4-epibrassinolide, jasmonic acid and their signaling inhibitors by regulating endogenous phytohormones - Li, Jiajia; Javed, Hafiz Umer; Wu, Zishu; Wang, Lei; Han, Jiayu; Zhang, Ying; Ma, Chao; Jiu, Songtao; Zhang, Caixi; Wang, Shiping (Frontiers in Plant Science, 2022)
Grape berries contain a variety of metabolites, such as anthocyanins, sugars, fatty acids, and antioxidants. Endogenous phytohormones strongly influence these metabolites, which regulate berry quality improvement. In this study, we evaluated the effects of 2,4-epibrassinolide (EBR, brassinolide (BR)-like growth regulator), jasmonic acid (JA), and their signaling inhibitors brassinazole (Brz), and sodium diethyldithiocarbamate (DIECA) on berry quality and antioxidant ability. Overall, the pre-harvest application of 0.5 mg L-1 EBR and 100 μmol L-1 JA significantly influences the quality of the grape berry. Results showed that EBR was superior to other treatments at enhancing the content of different metabolites, including anthocyanins, fructose, glucose, and a variety of fatty acids, in grapes. EBR and JA also enhanced the synthesis of gibberellin3 (GA3), cytokinin (CTK), salicylic acid (SA), JA, methyl jasmonate (MeJA), BR, and abscisic acid (ABA), while inhibiting the synthesis of auxin (IAA). Most genes related to BR/JA and anthocyanins/sugars/fatty acids biosynthesis were up-regulated. The effects of Brz and DIECA on the grape berry quality were totally reversed throughout the study, as shown by EBR and JA. According to correlation analysis, EBR and JA have a beneficial positive interaction that promotes the formation of strong coherences in grape berries between ABA/IAA/ZT-fruit expansion, BR/JA/MeJA/GA3/ZR-biochemical characteristics development, JA/MeJA/ABA/GA3/SA/ZR-antioxidant capacity enhancement, and JA/MeJA/IAA/GA3/ZT/ZR-fatty acids accumulation. In this regard, we concluded that preharvest exogenous 0.5 mg L-1 EBR and 100 μmol L-1 JA is a successful way to improve grape berry quality.